Innovation in Financial Management: New Strategies for Enhancing Efficiency and Company Performance - Utami, Suryandari Sedyo; Rofi'ah; Avira, Silvia; Setyaningsih, Endang (Global Writing Academica Researching & Publishing, 2024)
This research investigates the impact of adopting innovative technology in financial management on operational efficiency, financial decision-making, and reducing administrative costs in various companies. By focusing on the implementation of Fintech, Big Data Analytics, and financial process automation, this research finds that these innovations significantly improve company performance in facing the challenges of a dynamic business environment. This research uses a qualitative combination approach. A quantitative approach is used to measure impact numerically and carry out statistical analysis of the data collected. Data for this research was obtained from relevant academic literature, and case studies of companies that have implemented innovations in financial management. The analysis shows that managerial support, ease of use of technology, and organizational readiness to adapt are important factors in the successful implementation of innovation. The results highlight the importance of integrating technology in financial management practices to improve internal processes and better prepare companies for the future.